Loop-mediated isothermal amplification (LAMP) for rapid detection of Salmonella in foods based on new molecular targets. (May 2021) - Shang, Yuting; Ye, Qinghua; Cai, Shuzhen; Wu, Qingping; Pang, Rui; Yang, Shuanghong; Xiang, Xinran; Wang, Chufang; Zha, Fei; Ding, Yu; Zhang, Yinzhi; Wang, Jiasheng; et al.
Abstract: Various molecular techniques have been introduced for Salmonella detection. Loop-mediated isothermal amplification (LAMP) is a simple and easy-to-operate detection method compared with conventional PCR. However, the specificity and efficiency of DNA amplification relies on the selected target sequence. In this study, we aimed to identify new molecular targets and develop a LAMP-based method for the rapid detection of Salmonella in food samples. Using bioinformatics analysis and PCR verification, 3 and 10 molecular targets respectively unique to Salmonella genus and S. enterica were identified. The limit of detection (LOD) for these targets ranged from 2.1 × 10 2 to 2.1 × 10 3  CFU/mL. Of these, the ssaQ gene yielded 100% positive results upon testing with 23 most commonly reported Salmonella serovars and showed no cross-reaction with 22 non- Salmonella strains. Furthermore, its LOD was 2.1 × 10 1  CFU/mL, making it 10-fold more sensitive than the optimal PCR-based method. Therefore, the ssaQ gene was selected as the target gene to detect Salmonella using LAMP. The ability of the ssaQ -based LAMP method of detecting Salmonella in food samples was consistent with that of the standard culture method. The developed method has potential applications in identifying Salmonella contamination in food as well as for rapid and precise tracing of contamination sources in clinical diagnostics. Highlights: We developed a LAMP-based method for rapid detection of Salmonella in food samples. Bioinformatic and PCR analyses identified 13 Salmonella- specific molecular targets. The ssaQ gene was used as the target gene to detect Salmonella in LAMP. The detection limit of the ssaQ -based LAMP was 10-fold that of PCR.